2021
DOI: 10.12890/2021_002248
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal Muscle Cavernous Haemangioma: A Chest Wall Pandora’s Box: Intercostal muscle cavernous hemangioma

Abstract: Background: Haemangiomas are uncommon chest wall tumours arising outside the rib cage. Their occurrence in intercostal muscle is extremely rare. Aim: We describe a case of intercostal muscle cavernous haemangioma as a differential diagnosis for chest wall swelling. Case description: We describe an 18-year-old male patient with an asymptomatic left-sided chest wall swelling. Contrast-enhanced computed tomography revealed a well-defined homogenously non-enhancing mass lesion arising from the seventh intercostal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…At present, the most commonly used classification system is based on the type of vascular structure, which includes 5 subtypes: capillary hemangioma, cavernous hemangioma, VH, arteriovenous hemangioma, and mixed hemangioma. [5] Pathology confirmed that both tumors in our patient were VHs. Although IH is a benign tumor, it is somewhat aggressive.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…At present, the most commonly used classification system is based on the type of vascular structure, which includes 5 subtypes: capillary hemangioma, cavernous hemangioma, VH, arteriovenous hemangioma, and mixed hemangioma. [5] Pathology confirmed that both tumors in our patient were VHs. Although IH is a benign tumor, it is somewhat aggressive.…”
Section: Discussionsupporting
confidence: 76%
“…[10,14] IHs are usually considered to be congenital or due to trauma. [5,6] Our patient had no history of chest trauma, but had MHHs. Hemangiomas can be divided into a variety of subtypes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…IMH is frequently found in the muscles of the upper and lower extremities; intercostal IMH represents 1.2–1.4% of all IMH diagnoses [ 2 , 3 ]. We identified 8 published articles in which patients were pathologically diagnosed with either intercostal IMH or hemangioma originating in the intercostal muscle (Table 1 ) [ 5 12 ]. In these articles, the mean age at surgery was 27.6 years (range, 11–46 years), and there were only 2 female patients.…”
Section: Discussionmentioning
confidence: 99%